CS Quantity Is Not CS Quality. - Raghavendra Rao Loka (Communications of the ACM, 2015)
The article presents a letter concerning the Editor's Letter “Incentivizing Quality and Impact in Computing Research," by Moshe Y. Vardi from the May 2015 issue.